Selecting convexity to improve and maintain peristomal skin integrity. (10th September 2020) - Evans, Moira; White, Pamela
Abstract : Each person with a stoma is an individual who may react differently when faced with similar situations and, as such, each patient needs to be considered on a person-by-person basis to address their needs, support their acceptance of living with a stoma, as well as to encourage their rehabilitation. This article discusses the benefits that a convex flange can offer ostomates to reduce and minimise leakage episodes and in doing so support peristomal skin integrity and, in particular, the benefits of a convex pouch with a hydrocolloid flange containing medical grade Manuka honey. It reports on the findings of an independent nurse study, which included discussions about the varying types of convexity offered to ostomates, following an assessment of patients' needs.